Renin-Angiotensin System Past, Present and Future - Naidenova Tolekova, Anna (IntechOpen, 2017)
Exploring the contractile activity of smooth muscle segments isolated from various organs of healthy animals and animals with experimentally induced diabetes, she obtained original data about angiotensin II-induced force and time parameters. For the first time, she established the effect of ghrelin on angiotensin II-provoked contraction of the urinary bladder. Original data on the role of both types of angiotensin receptors for the contractile activity of the various segments of the gastrointestinal tract and bladder were obtained. By applying specific software for force and time parameter analysis, the contribution of different types of angiotensin receptors on muscle contractility has been shown. The new methodology was used to analyze the data obtained during the registration of smooth muscle relaxation activity, which allows the determination of not only the magnitude of the mechanical response but also the parameters related to the time and speed of the contractions. Plasma renin activity models have been developed using mathematical approaches to predict the effect of different drug doses on the behavior of the system.